Citric acid (ph 7.8) treatment of avulsed teeth Alan Q. Hans. - Hans, Alan Q.
The teeth of two dogs (11, 21, 22) were extracted and allowed to dry outside the oral cavity for one hour and a half before any interceptive-corrective procedures were done. After R.C.T., the experimental teeth (21, 22) were immersed in citric acid pH 7.8 for 20 minutes, then re-planted along with the control tooth 11 at the same time, so that the extra-oral time of all the teeth were more or less the same. The animals were sacrificed six weeks after the "avulsion" and replantation, and histologic sections were taken for a definite, final, and conclusive diagnosis.